Structural Performance of Double castellated Steel Beams with Innovative Opening Configuration - Naji, Ayat; Kadhim, Mushriq Fuad (Engineering, Technology & Applied Science Research, 2025)
This research delves into the structural performance of castellated steel beams featuring expanded webs, emphasizing how design variables, such as the number of openings and cutting angle, affect the load capacity, deflection, and stiffness. Castellated beams are engineered to improve the strength-to-weight ratio of the standard I-beams by cutting and reconstructing the web into hexagonal, rectangular, or circular openings. This configuration not only boosts the beam load capacity and minimizes weight, but also maintains or enhances stiffness, rendering it well-suited for long-span structures. In the present study, seven beam specimens were tested under one-point load conditions, including six castellated beams. The key findings demonstrate that reducing the number of openings significantly increases the load capacity and reduces deflection. The castellated beams outperformed RB-S by up to 68.9% in the load-carrying capacity at Service Limit Deflection (SLD). Additionally, the study examined the influence of cutting angles (58°, 52°, and 45°) on the beam performance, concluding that a 52° angle provided the best balance between strength and stiffness. The results underscore the importance of optimizing castellated beam designs for large-scale construction applications, where balancing weight reduction, structural integrity, and serviceability is crucial.